Back to Basics: The Importance of Conceptual Clarification in Psychological Science. (August 2022) - Bringmann, Laura F.; Elmer, Timon; Eronen, Markus I.
Although the lack of conceptual clarity has been observed to be a widespread and fundamental problem in psychology, conceptual clarification plays a mostly marginal role in psychological research. In this article, we argue that better conceptualization of psychological phenomena is needed to move psychology forward as a science. We first show how conceptual unclarity seeps through all aspects of psychological research, from everyday concepts to statistical measures. We then turn to recommendations on how to improve conceptual clarity in psychology, emphasizing the importance of seeing research as an iterative process in which it is necessary to revisit the phenomena that are the foundations of theories and models, as well as how they are conceptualized and measured.